The Influence of Using Natural Language Processing (NLP)-Based Generative Artificial Intelligence on 21st Century Skills in Higher Education: A Quantitative Analysis - Junaedi, Mahfud; Hasanah, Silviatul; Nasikhin, Nasikhin (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2024)
This study aims to analyze the effect of using natural language processing (NLP)-based generative artificial intelligence on 21st-century teaching skills. This research is quantitative using the simple linear regression analysis method. The research sample consisted of 270 students at Walisongo State Islamic University Semarang. The main focus of this study was to explore the relationship between the use of NLP-based generative AI and four 21st-century skills, namely critical thinking, problem-solving, collaboration, and communication. The results of the statistical analysis showed that the use of this AI had a significant influence on all four skills. Collaboration (Y3) is the skill most influenced by AI with a P-value of 0.000 and a t-count of 4.36, indicating that AI strengthens individuals' ability to cooperate and coordinate in teams. Critical thinking (Y1) ranked second with a P-value of 0.001 and a t-count of 3.47, indicating that AI promotes analytical and evaluative skills. Problem solving (Y2) also showed a significant effect with a P-value of 0.001 and a t-count of 3.41, indicates that AI helps in finding innovative and effective solutions to complex problems. Meanwhile, communication (Y4) was the least influenced skill, with a P-value of 0.005 and a t-count of 2.83, although it remained significant.